IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT (P5) AT SDN PODOKOYO 2 - Susilo, Joko; Aura, Nindya; Alqibtiyah , Mariah; Rizqi Tsania, Indah; Fanissa, Sintania (Antis-publisher, 2025)
Objective: This study aims to implement the Pancasila Student Profile Strengthening Program (P5) at SDN Podokoyo 2, focusing on character development through project-based learning while enhancing digital literacy among students and parents. Method: A mixed-method approach was employed, combining training sessions, collaborative project activities, and structured evaluations. Students engaged in hands-on projects that emphasized teamwork, creativity, and motor skill development, while parental involvement was facilitated through digital literacy workshops. Results: The findings indicate that 80% of students successfully completed the assigned projects, demonstrating improved problem-solving and collaboration skills. Additionally, 83% of participants reported satisfaction with the activities, highlighting the program's effectiveness in fostering both cognitive and socio-emotional competencies. Novelty: This study integrates digital literacy training within the P5 framework, emphasizing the role of parental engagement in supporting student learning. The results contribute to the discourse on holistic education by showcasing the synergy between character education, technological adaptation, and community involvement. Future recommendations include strengthening partnerships with educational stakeholders and diversifying training content to enhance student adaptability in a digital era.